Development Of Simulator Training Centre For The Manufacturing Of Automative Seating - Zainul Abidin, Siti Nursyafiqa (2017)
In the manufacturing industry, the operator who conduct the process has been the crucial foundation of the organization. They are the basic fundamental of frame work that runs the industry. Many of the industry still using the operator to conduct the process manually which means the operation operates based on the skill level of the operator. The quality of product produced by the industry is depends on the skill of operator who conduct the process. The purpose of this study is to develop a training centre for the manufacturing of automotive seating. In this study, we want to analyze the quantify measurement to evaluate operator skill and competencies. This is due to our weak evaluation measurement system of operator skill which only based on On Job Training conducted by the supervisor. There are no valid evidence to quantify the skill of operator. Through this study, we want to develop a simulation training centre which reflects the actual process in the manufacturing process. The training that reflects the actual condition in the manufacturing process is the best practices to develop the skill of operator based on actual condition.